The impact of customer satisfaction on customer loyalty among MPC’s clients in East Coast Region (Pahang) / Halimah Ahmad Mahauddin - Ahmad Mahauddin, Halimah (Faculty of Business and Management, 2010)
The objective of this research is to identify the customer satisfactions level towards CSF that affecting customer loyalty among the MPC’s clients, to know the relationship between the factors that contributes the customer loyalty (customer satisfaction with product or services, price, and serviceperson) and customer loyalty, and to determine other factors which may become top reasons of using MPC service, complaints, and recommends by the MPC’s clients, which may shape the customer loyalty. This research focused on MPC’s clients from east coast region mainly in Pahang area only. The independent variables involve in this research were customer satisfaction with MPC’s products or service, price, and serviceperson. Researcher had use the random sampling by distribute any organizations that become MPC’s clients from MPC’s customer mailing list databases and distribute convenience where anyone in the company which were selected by random sampling from could answers the survey form. Researcher also used the Cronbach’s Alpha to analyze the questionnaires reliability, using the Correlation analysis and Multiple Linear Regressions to the relationship and the significant between dependent variable and independent variables, and used the Cross Tabulations to determine which type of business in this research determined the degree of selected items in each independent variable. All variables have low and weak positive relationship for products or services and moderate relationship for price and serviceperson, but all the variables has significant value, based on the correlation and regression test. The degree of relationship is price, followed by serviceperson, and the last is products or services. Therefore, all alternative hypotheses are accepted. Thus, from the findings, it is recommended for MPC to sustain but with some improvement its products or services, price and serviceperson.